Aortic dissection in pregnancy in England: an incidence study using linked national databases. Issue 8 (20th August 2015) - Banerjee, Amitava; Begaj, Irena; Thorne, Sara
Abstract : Objectives: To conduct the first population-level incidence study of aortic dissection in pregnancy using linked hospital-based data in England. Setting: Hospital-based data (Hospital Episode Statistics (HES) linked with mortality data from the Office of National Statistics), national enquiries (Confidential Enquiries into Maternal Mortality) and surveys (UK Obstetric Surveillance System; UKOSS) of aortic dissection in pregnancy from 2003 to 2011 in England. Participants: Between 2003 and 2011, all female patients admitted with diagnoses of aortic dissection (not necessarily as the primary cause of admission) and of pregnancy, childbirth and puerperium, were included. Outcome measures: Diagnosis of aortic dissection during pregnancy, operated or not operated, with outcome of death or live patient from 2003 to 2011 in England. Results: There were significant differences in characteristics of databases with respect to study population, time of study, recorded event and follow-up of outcomes. On the basis of HES, annual incidence of aortic dissection was 1.23 (95% CI 1.22 to 1.24) per 100 000 maternities. Incidence of aortic dissection with death within 1 year was 0.30 (0.29 to 0.31) per 100 000 maternities. Incidence of aortic dissection increased from 0.74 (0.73 to 0.75) per 100 000 maternities in 2003–2005 to 1.52 (1.51 to 1.53) per 100 000 maternities in 2009–2011. In the Confidential Enquiries into Maternal Deaths, incidence of deaths was highest for 2003–2005 (0.43/100 000 maternities) and lowest for 1997–1999 (0.21/100 000 maternities). In the UK Obstetric Surveillance System, national incidence of aortic dissection was 0.80 (0.50 to 1.50) per 100 000 maternities between 2009 and 2011. Conclusions: The case of aortic dissection in pregnancy illustrates data limitations regarding complications in pregnancy from different sources in the UK, even for a diagnosis with seemingly few alternative coding and diagnostic possibilities. These limitations should be acknowledged when estimating incidence and outcome.